Upaya Meningkatkan Aktivitas dan Hasil Belajar Siswa pada Materi Interaksi Sosial Melalui Model Pembelajaran Teams Games Tournament - Juliati Juliati (2022)
This study aims to determine the increase in student activity and learning outcomes in Social Interaction through the Teams Games Tournament (TGT) learning model. The research subjects were students of class VII-6 of SMP Negeri 3 Banda Aceh in the odd semester of the 2021/2022 academic year as many as 32 students consisting of 15 male students and 17 female students. This research is a classroom action research which consists of two cycles. Each cycle consists of four stages, namely planning, implementation, observation and reflection. The implementation of the action is carried out in two meetings in each cycle. The data obtained were analyzed using qualitative and quantitative descriptive statistical analysis. The results showed that the application of the Teams Games Tournament (TGT) cooperative learning model could increase student learning activities on the subject matter of Social Interaction with a percentage of 64.06% (quite active) in the first cycle and 85.93% (very active) in the second cycle. The application of the TGT type cooperative learning model can also improve student learning outcomes in the material of social interaction with the percentage of classical learning completeness 63.6% in the first cycle and 81.8% in the second cycle. Based on the results of the study, it was concluded that there was an increase in the activity and learning outcomes of class VII-6 students of SMP Negeri 3 Banda Aceh through the application of the Teams Games Tournament (TGT) type of cooperative learning model.